PENINGKATAN MOTIVASI DAN HASIL BELAJAR IPS MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN MEDIA CLASSROOM PADA SISWA KELAS VII SMP ZION MAKASSAR - Vinsensia Lusia Lodan; Nawir Rahman,; Nurdin . (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2022)
This study aims to determine the increase in motivation and learning outcomes of class VII SMP Zion Makassar.. This research is a Classroom Action Research. The subjects of this study were students of class VII SMP Zion Makassar. Data collection uses documentation, observation, questionnaire and test techniques. The validity of the data using source triangulation techniques and triangulation techniques. The data analysis technique went through three stages, namely data reduction, data presentation and conclusion drawing. The results of the research conducted are 1). The students' learning motivation in the high category from the first cycle was 60% or 18 students and in the medium category it was 40% or 12 students. 2). Student learning outcomes before the action only reached 30%, namely 9 students who completed. After the action, in the first cycle increased to 55%, namely 17 students who completed. After the second cycle, there was an increase to 90%, namely 27 students who completed. Based on the research results, problem-based learning can increase student motivation and learning outcomes.Keywords: learning motivation, learning outcomes, problem based learning, classroom